Comparison Between Magnetic Resonance Imaging and Arthroscopy Findings in Medial Meniscal Injuries - Agrawal, Sumit (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: Identification of deranged structure in the knee requires keen sense of clinical judgement, imaging modalities, arthroscopy and at times surgical exploration. Magnetic resonance imaging and arthroscopy have shown good diagnostic performance in detecting lesions of the menisci and hence this study was carried out to compare magnetic resonance imaging and arthroscopic findings in medial meniscus injury. METHODS: The present study comprised of30 male and 5 female patients, age ranging between 20 to 60 years. This prospective study was done over a period of two and half years in Kasturba Medical College, India. A total of 35 patients were included in this study. Cases suggestive of meniscal injury underwent both and their findings were compared. Statistical calculation was performed using Microsoft excel version 7 and SPSS 13 statistical program. RESULT: The magnetic resonance imaging of 35 knees showed that there were tears in 31 patients, predominantly in the posterior horn (17). Tears in anterior horn and bucket handle tears were equal in number (7 each). The magnetic resonance imaging did not detect any tear in 4 patients. When the knees were subjected to arthroscopic examination tears were seen in 30 patients of which most were posterior horn tears (18), followed by bucket handle tears (7) and anterior horn tears (5). Arthroscopy detected no tear in 5 patients. Of the 4 patients having normal Magnetic Resonance imaging 1 patient showed tear on Arthroscopy. In the rest 3 patients Arthroscopy confirmed the normal finding of MRI. CONCLUSION: Magnetic Resonance imaging is highly accurate in diagnosing medial meniscal injuries of the knee and can be used as a first line diagnostic tool in patients with suspected medial meniscal injuries. Magnetic Resonance imaging is the most appropriate screening tool for therapeutic arthroscopy.